Synthesis of Dibenzyls by Nickel-Catalyzed Homocoupling of Benzyl Alcohols - Pan, Feng-Feng; Guo, Peng; Huang, Xiaochuang; Shu, Xing-Zhong (Synthesis, 2021)
Dibenzyls are essential building blocks that are widely used in organic synthesis, and they are typically prepared by the homocoupling of halides, organometallics, and ethers. Herein, we report an approach to this class of compounds using alcohols, which are more stable and readily available. The reaction proceeds via nickel-catalyzed and dimethyl oxalate assisted dynamic kinetic homocoupling of benzyl alcohols. Both primary and secondary alcohols are tolerated.
Keywords: homocoupling; nickel; dibenzyls; alcohols; synthetic methodology